AWARENESS ABOUT ROXOLID IMPLANTS AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Roxolid implants are endosseous root-form implants made of an alloy comprising 85% titanium and 15% zirconium. This unique combination greatly improves the tensile and fatigue strengths of implants compared to the ones manufactured with commercially pure titanium and its alloys.The aim of the study was to assess the awareness about roxolid implants among dental students.This was a questionnaire-based cross-sectional type of study comprising 100 dental college students in Chennai. A self-designed questionnaire contains 10 questions based on the knowledge and awareness of the Roxolid implant system among dental college students. Questionnaires were circulated through an online website survey planetThe questions explored the awareness on using Roxolid implants, their indications, contraindications and clinical advantages. After the responses were received from 100 participants, data was collected and analysed.37% are aware about Roxolid implants . 33% are aware of the indications of Roxolid implants . 25% are aware of the contraindications of Roxolid implants . 23% are aware of the clinical advantages of Roxolid implants.3% use Roxolid implants. The awareness about Roxolid implant systems was moderate among dental students.Hence, more intensive educational and awareness programs need to be initiated to improve the knowledge and application of Roxolid implants in clinical practice.